Improving Efficiency of Dust Removal from Surfaces to Maximize Output of Photovoltaic Cells - Sehdev, Sancia; Gureja, Manya; Sukhija, Mandeep (International Journal of Computer Sciences and Engineering, 2020)
The series of experiments documented in this paper was aimed at determining, analyzing and comparing different solar panel cleaning systems. Output in all experiments was measured in terms of Potential Difference, Current and Power. Readings were taken under three circumstances: (i) when the solar panel was clean, (ii) when a measured amount of material was deposited on it, and (iii) after cleaning action was performed. It was observed and concluded through performed experiments that (i) Of materials used (talcum, dust, sawdust, and leaves), dust was most difficult to remove and led to a maximum drop in the overall output of solar panel after cleaning action was performed, (ii)Dust particles are charged in nature and stick to solar panel screens, rendering current mechanical cleaning methods inefficient, and (iii) Electrodynamic sheet comprising of Indium Tin Oxide improved efficiency to up to 98% whereas other methods witnessed a power drop to a maximum of 25% of original power output, making it better than mechanical cleaning methods by a significant margin.